The relationship between ineffective peripheral perfusion and Anemia: case study - Kusumawati, Heni (Sean Institute, 2024)
Anemia is a condition characterized by reduced hemoglobin (Hb) in the body. Hemoglobin is a metalloprotein, a protein containing iron in red blood cells that carries oxygen from the lungs to the rest of the body. Anemia is a condition in which the body experiences a lack of red blood cells, causing the body's organs not to receive enough oxygen, making anemia sufferers have pale skin and get tired quickly. The general aim of this scientific paper is to examine the relationship between ineffective peripheral perfusion and Anemia through nursing care. The research design used was a case study which explored the problem of nursing care for patients who experienced Anemia at Misi Lebak Hospital for three days for Mrs. S. Data collection can be done through interviews, observation, physical examination and documentation. The results of the assessment obtained were that the patient complained of weakness, nausea, and vomiting. Assessment results: anaemic conjunctiva, blood pressure 80/60 mmHg, breathing 20x/minute, pulse 87x/minute, body temperature 36.8°C, could only eat food ½ portion, BW before illness 45 Kg, BW during illness 44 Kg, TB 156 Cm, BMI: 18.33 with underweight interpretation, laboratory examination results show, Hemoglobin 7.6 g/ dL, Leukocytes 18,960 /µL. Problems that arise are ineffective peripheral perfusion, nutritional deficits, activity intolerance, and risk of infection. The implementation provides educational actions, teaches an iron diet program to improve circulation, recommends small but frequent meals and monitors food intake, monitors physical fatigue, and monitors signs and symptoms of local and systemic infections, in addition to collaborating with the medical team in administering transfusions, antibiotic therapy, and anti-nausea as well as collaborating with the Nutrition team in providing an iron diet. Nursing problems can be resolved on the third day with the criteria for Hb results increasing to 10.2 g/ dL, systolic and diastolic blood pressure improving to 120/80 mmHg, the portion of food consumed increasing to 1 portion, complaints of fatigue decreasing, the patient being able to carry out activities, white blood cell levels improved to 10,500 /µL.